2001
DOI: 10.1097/00042192-200103000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to sexual function in postmenopausal women with a history of breast cancer

Abstract: In this small sample of BCS, we found multiple correlates of sexuality. Most seem to impact uniquely on individual domains of sexual function. Several characteristics are modifiable and could be targets for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 42 publications
5
50
0
7
Order By: Relevance
“…Marital satisfaction has a close relationship with sexual relationship, as an effective factor, in improving interpersonal relationships and some outcome aspects of the disease [21][22][23][24]. The prevalence of sexual disorder in women with breast cancer varies between 21-94% [12,[25][26][27]. The differences vary according to the assessment of different sexual phases, time of assessment, kinds of treatment and special matters such as psychological, cultural, philosophical or religious viewpoints toward sex and cancer [11,18,28].…”
Section: Discussionmentioning
confidence: 99%
“…Marital satisfaction has a close relationship with sexual relationship, as an effective factor, in improving interpersonal relationships and some outcome aspects of the disease [21][22][23][24]. The prevalence of sexual disorder in women with breast cancer varies between 21-94% [12,[25][26][27]. The differences vary according to the assessment of different sexual phases, time of assessment, kinds of treatment and special matters such as psychological, cultural, philosophical or religious viewpoints toward sex and cancer [11,18,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, the one study to examine serum testosterone in breast cancer survivors found that those with higher levels actually had less desire for sex. 19 This unexpected finding may reflect the association in postmenopausal women between obesity and higher circulating androgen levels. Randomized trials show benefits of testosterone replacement in women presenting with low desire after bilateral oophorectomy.…”
Section: Sexual Function Gender and Damage From Cancer Treatmentmentioning
confidence: 95%
“…Two studies report QOL scores comparable to healthy controls [10,12]. However, not inconsequential numbers of survivors have reported lingering effects of their treatment, especially menopausal symptoms [4,8,13,14], arm and chest wall problems [7,10,15], weight gain [7], cognitive impairment [7], sexual difficulties with partners [4,8,10,[15][16][17], problems with obtaining and maintaining health insurance, and fears of recurrence [8,15,18]. Almost a third of the women continue to report psychological distress, primarily depression [15][16][17][18][19][20][21].…”
Section: Health and Quality Of Life Among Long-term Breast Cancer Surmentioning
confidence: 99%